(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Medical cyber-physical networks (MCPNs) have the potential to totally alter the healthcare business since they make it feasible to remotely monitor, diagnose, and treat patients. Despite this, MCPN usage is increasing at a startling rate, which raises concerns about security and privacy. Safe data retrieval is critical for maintaining the privacy and accuracy of patients’ medical information. The challenges of securing data retrieval in MCPNs, as well as the existing solutions, are the major emphasis of this paper, which provides a review of the relevant literature. Some of the procedures and strategies discussed include access control, encryption, authentication, data masking or pseudonymization, and safe data storage. The challenges of implementing these safety measures and minimising the effect of human variables are also explored. The healthcare sector must maintain its investment in robust security measures to ensure the safety and privacy of patients and the confidentiality of their medical information. If proper safeguards are in place, the usage of MCPNs has the potential to dramatically alter healthcare and lead to improved results for patients.